Síndrome metabólica e aterosclerose subclínica em adolescentes: Uma avaliação dos critérios diagnósticos - Oliveira, Renata Cardoso (2016)
Introduction: epidemiological evidence show strong links of the metabolic syndrome with subclinical atherosclerosis. Objective: to identify the best diagnosis of metabolic syndrome criteria to detect thickening of the intima-media complex of the carotid in adolescents. Methods: cross-sectional study with a quantitative approach, developed in 512 adolescents from public schools aged between 15 and 19 years between September 2012 and June 2013. For diagnosis of metabolic syndrome were used two criteria of the International Diabetes Federation and the NationalCholesterolEducationProgram / AdultTreatmentPanel III adapted by Cook. It was considered marked thickening of the average complex carotid intimal, when the value was equal to or greater than + 2Z. To evaluate the association between the criteria of the metabolic syndrome and thickening of the intimal average carotid complex we used the chi-square test was also evaluated the positive and negative preditivio value of each criterion to detect thickening. To verify the agreement of the two diagnostic criteria was used the Kappa test. We used SPSS version 22.0 and 95% confidence interval. Results: metabolic syndrome and systolic blood pressure changes identified by NationalCholesterolEducationProgram / AdultTreatment PanelIII adapted by COOK was associated with thickening of the intima-media complex-carotid (p = 0.020, p = 0.030, respectively). Metabolic syndrome was diagnosed by two criteria in 19.2% (<0.001) with low agreement, kappa of 0.28. The diagnostic criteria that had the highest positive predictive value was NationalCholesterolEducationProgram / AdultTreatmentPanel III adapted by COOK 15%. Conclusion: the NationalCholesterolEducationProgram / AdultTreatmentPanel III adapted by COOK was the criterion that was associated with the presence of thickening of the intima-media complex of the carotid.